Formulation and evaluation of irbesartan microspheres - Y. Deepika; A. Pavani; M. Bhagavan Raju (International Journal of Pharmacy and Analytical Research, 2022)
Microspheres are characteristically free flowing powders consisting of proteins or synthetic polymers of biodegradable nature. Microspheres are particles between 0.1 and 200 μm in size. A well designed controlled drug delivery system can overcome some of the problems of conventional therapy and enhance the therapeutic efficacy of a given drug. There are various approaches in delivering a therapeutic substance to the target site in a sustained controlled release fashion. A Microspheres has its drug dispersed throughout the particle i.e. the internal structure is a matrix of drug and polymeric excipients. It is the reliable means to deliver the drug to the target site with specificity, if modified, and to maintain the desired concentration at the site of interest without untoward effects. Microspheres received much attention not only for prolonged release, but also for targeting of anticancer drugs to the tumour. Microspheres are spherical micro particles, and are used where consistent and predictable particle surface area is important. In microspheres drug is located centrally within the particle, where it is encased within a unique polymeric membrane. In future by combining various other strategies, microspheres will find the central place in novel drug delivery, particularly in diseased cell sorting, diagnostics, gene & genetic materials, safe, targeted and effective in vivo delivery.